Anti-hyperglycemia Effects of Plant Secondary Metabolites Towards PKA/CREB Pathway Activation in Diabesity - Bhumica Kiran (International Journal of Biochemistry and Biomolecule Research, 2024)
Objective: Diabesity, the amalgamation of diabetes and obesity, presents a significant global health challenge. This research carefully examines how plant secondary metabolites influence glucose regulation in diabetes using the PKA/CREB pathway, paying particular attention to diabesity—the combination of diabetes and obesity. Understanding the complex ways in which these metabolites affect metabolic health will help to identify new treatment approaches for managing diabetes and its associated problems. By conducting a thorough analysis, this research aims to provide essential insights into the creation of focused interventions that will ultimately improve the management of metabolic disorders in general and the health of the general public by addressing the various challenges presented by obesity. Methods: The study aimed to evaluate the efficacy of various phytochemicals against diabetes using computational techniques to target the proteins 4uj1 and 6e99. Protein structures were validated using PDBsum and BIOVIA Discovery Studio. Molecular docking, facilitated by PyRx, utilized data from PubChem and molecular structures from Indian medicinal plants. Ligands were pharmacologically assessed using ADMET filters. This comprehensive approach, integrating multiple data sources and computational methods, offers deep insights into potential anti-diabetic medications. The use of advanced technologies such as molecular docking and protein structural validation enhances our understanding of the therapeutic potential of natural compounds in diabetes management. The results highlight the importance of combining traditional knowledge with modern scientific techniques to develop effective treatments, suggesting that compounds from Indian medicinal plants may offer novel strategies for treating diabetes and related metabolic disorders. Results: Molecular docking experiments identified Ginkgolides, Nimbin, tetrandrine, emblicanin A, and ginsenosides as ligands with the lowest binding affinities to the target proteins, indicating their potential as anti-hyperglycemic agents. Conclusion: Nimbin, due to its low binding affinity for the proteins 4uj1 and 6e99, shows promise for diabetes therapy through the PKA/CREB pathway. This finding underscores the significance of Nimbin in ongoing diabetes research and clinical trials, highlighting its potential for developing new treatment strategies.
Keywords: Diabetes; Diabetes mellitus; PKA/CREB pathway; Type 1 DM; Type 2 DM; anti-hyperglycemia; obesity